TEKNIK BUDIDAYA DAN PASCA PANEN IKAN NILA SALIN BAGI MASYARAKAT PEMBUDIDAYA DI DESA SEDARI, KECAMATAN CIBUAYA, KABUPATEN KARAWANG - Pramono Adi, Catur (Fakultas Pertanian_Universitas Tidar, 2022)
Cibuaya District, Karawang Regency, was designated as a Fish Cultivation Village in 2022. Then to increase awareness of coastal communities, especially fish cultivators, on the importance of the community's role for the welfare of family members from fish farming businesses. This activity is a form of community service from the Fishery Product Processing Engineering Study Program at the KP Karawang Polytechnic as a form of implementing the third dharma of the Tridharma of Higher Education. Activities and continuity of community service are actually very important both for university managers as well as for the existence of these universities in the community. Community service with the topic of